Behaviour of CFRP confined square concrete-filled stainless steel tubular columns under uni-axial compression. (February 2023) - Tang, Hongyuan; Wang, Huixiang; Liu, Ye; Sun, Xujie; Huang, Xiaogang
Abstract: To study the behaviour of the carbon fibre-reinforced polymer (CFRP) confined square concrete-filled stainless steel tubular (CFSST) stub column, three square CFSST stub columns and nine CFRP confined square CFSST stub columns were tested under axial compression. The test parameters included the number of CFRP sheet layers and the thickness of the stainless steel tube. The test results showed that failure modes of all CFRP confined square CFSST stub columns were the fracture of CFRP sheets and the outward local buckling of the stainless steel tube at the chamfering. The typical load–displacement curves of the tested columns exhibited four stages, i.e., elastic stage, elastoplastic stage, descending stage and residual stage. CFRP sheets could restrain the local buckling of CFSST, and improve the ultimate bearing capacity and the ductility index of the columns. With the increase in the number of CFRP sheet layers and the wall thickness of the stainless steel tube, the bearing capacity of the column increased linearly. Based on the twin-shear unified strength theory, a calculation method of the ultimate bearing capacity of the square CFSST stub column was proposed. Besides, through the superposition method and regression analysis, two simplified methods to predict the ultimate bearing capacity of CFRP confined square CFSST stub column under axial compression were obtained. Highlights: 12 CFRP confined squared CFSST stub columns were prepared and tested under uni-axial compression. The effect of CFRP layers, thickness of stainless-steel tube on the uni-axial behaviour of the column was investigated. The ultimate bearing capacity of the column was calculated based on the twin-shear unified strength theory. Two simplified methods were proposed to predict the ultimate bearing capacity of the column.